Extended Alkenyl and Alkynyl Benzotriazoles with enhanced Two‐Photon Absorption properties as a promising alternative to Benzothiadiazoles - Torres-Moya, Ivan; Benítez-Martín, Carlos; Donoso, Beatriz; Tardio, Carlos; Martin, Raul; Carrillo, Jose Ramon; Diaz-Ortiz, Angel; Nájera-Albendín, Francisco; Prieto, Pilar; Perez-Inestrosa, Ezequiel (Wiley-VCH Verlag GmbH & Co, 2019)
A series of donor–p–acceptor–p–donor (D-p-A-p-D) benzoazole dyes with 2H-benzo[d][1,2,3]triazole or BTDcores have been prepared and their photophysical proper-ties characterized. The properties of these compounds dis-play remarkable differences, mainly as a result of the elec-tron-donor substituent. Dyes with the best properties havevisible-light absorption over l = 400 nm, large Stokes shiftsin the range of about 3500–6400 cm@1, and good fluores-cence emission with quantum yields of up to 0.78. The two-photon absorption properties were also studied to establishthe relationship between structure and properties in the dif-ferent compounds synthesized. These results provided crosssections of up to 1500 GM, with a predominance of S2! S0transitions and a high charge-transfer character. Time-depen-dent DFT calculations supported the experimental results.
Keywords: Fluorescencia; Two-Photon Absorption; Fluorescent Probes